Socio-demographics impact of healthy lifestyle in parents with preschoolers: a pilot study - Chitou, Eirini; Karavida, Vasiliki; Tympa, Eleni; Zachopoulou, Evridiki (Intelektual Pustaka Media Utama, 2025)
Parents’ ability to follow a healthier lifestyle is influenced by their socio-demographic characteristics. This study seeks to assess the lifestyles of preschoolers’ parents and discern potential correlations with their demographic attributes. Using a quantitative approach, a pilot study was conducted among 51 parents who actively participated in a survey. To study the extent of parents’ adoption of a healthy lifestyle, a 25-question Likert scale questionnaire was employed. Findings revealed a notable prevalence of healthy habit adoption, including a wholesome diet. Furthermore, the results noted a commendable level of parents’ knowledge of matters related to healthy lifestyles. Of particular interest was the significant impact of maternal fixed work schedules on the implementation of healthy eating habits, which surpassed the influence of other types of work schedules. Additionally, a direct correlation was observed between information derived from authoritative sources about healthy lifestyles and the educational attainment of parents. More specifically, parents with higher educational attainment tend to be more conscious of healthy living and to actively incorporate a healthy lifestyle into their daily routines. In light of these findings, there is a clear indication that further research into the dynamics of parents’ adoption of healthy lifestyles is required.